Sedimentation And Abrasion Identification in Cikidang Fishery Port and Surrounding Coastal Area - Idris, Muhamad Kemal; Setyaningsih, Wahyu Adi; Alimuddin, Alimuddin (Politeknik Negeri Batam, 2024)
Cikidang Fishery Port is one of the ports with serious abrasion and sedimentation problems. Seawater abrasion significantly affects some coastal areas that lack breakwater protection. Seawater abrasion causes the shoreline to recede further into the land, thereby narrowing the operational area of the coast. Not only that, harbour areas that are both protected and unprotected by breakwater also experience problems regarding water areas caused by ocean currents, tides, and large waves that lead to sedimentation. Sediment reduces the depth of harbour dock waters, making it impossible for ships to dock. As a fishing port that contributes significantly to the local economy, the Cikidang Fishery Port (CFP) necessitates analysis and solutions to address the issues of sedimentation and abrasion. References for this study used both primary and secondary data. We used a GPS handheld to measure the coastal area, and we conducted comparative studies using satellite images to gather secondary data. This will calculate the effective duration of the dredging process, enabling precise execution and minimizing the associated expenses.